A Bayesian-Estimated Model of Inflation Targeting in South Africa - Harjes, Thomas (IMF Working Papers; Working Paper ;, 2008)
This paper estimates a small dynamic macroeconomic model for the South African economy with Bayesian methods. The model is tailored to assessing the impact of domestic as well as external shocks on inflation within an inflation targeting framework, by incorporating forward-looking behavior of private agents and of the monetary authority. The model is able to display important empirical features of the monetary transmission mechanism that have been found in other studies. It helps to integrate the short-term inflation outlook into a consistent medium-term framework and to design the policy response for various shocks that affect inflation.